الذكاء الاستراتيجي و دوره في تحقيق الميزة التنافسية المستدامة بحث استطلاعي لآراء عينة من مدراء اقسام و مديري الشعب الادارية في جامعة كربلاء - A.L. Muhammad Awad Al-Shammari * A.L.Moued kadhim alasadi** L. Ahmاحمد حسين احمد الموسوي** موعد كاظم الاسدي** محمد عوض جارالله الشمري*ad Hussein Ahmad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
This research was presented in the light of a conceptual intellectual framework that included two key variables: Strategic Intelligence (independent) and sustainable competitive advantage (Dependent). Each variable has several dimensions, including strategic intelligence (foresight, systems thinking, future vision, motivation, partnership) and sustainable competitive advantage (core capabilities, creative culture, Information Technology, strategic flexibility). The University of Karbala has chosen a field of research, as the researchers relied on the questionnaire as a tool to obtain the required information, and the method of the intended sample was adopted to survey the opinions of the research sample of 104 individual from the directors of the scientific and administrative departments and people officials at the university , since (125) questionnaire was distributed, of which (113) was valid for analysis (104), The research objective to define the nature of the relationship between intelligence, strategy and sustainable competitive advantage, .The research found a range of findings, most notably a weak and intangible impact between strategic intelligence and sustainable competitive advantage.